As condições de trabalho docente e a pedagogia histórico-crítica: uma reflexão - Vanessa Moraes Abdala Guarda (Centro Universitário Salesiano de São Paulo, 2016)
This article aims to promote a brief analysis of how the working conditions of teachers may influence the development of the historical-critical pedagogy, and also how this approach can help the analysis of the current working conditions of teachers, from the design dialectics of Saviani theory. This article contemplates, albeit briefly, a reflection on the historical-critical pedagogy as a theoreticalmethodological fundamentals and some notes about the working conditions of teachers in order to discuss the implications of these conditions in the development of historical-critical perspective, from the recognition of the influence of historical, political and social conditions in education.